Longitudinal Survey of Coronavirus Circulation and Diversity in Insectivorous Bat Colonies in Zimbabwe - Vimbiso Chidoti (Viruses, 2022)
Background: Studies have linked bats to outbreaks of viral diseases in human populations such as SARS-CoV-1 and MERS-CoV and the ongoing SARS-CoV-2 pandemic. Methods: We carried out a longitudinal survey from August 2020 to July 2021 at two sites in Zimbabwe with bat–human interactions: Magweto cave and Chirundu farm. A total of 1732 and 1866 individual bat fecal samples were collected, respectively. Coronaviruses and bat species were amplified using PCR systems. Results: Analysis of the coronavirus sequences revealed a high genetic diversity, and we identified different sub-viral groups in the Alphacoronavirus and Betacoronavirus genus. The established sub-viral groups fell within the described Alphacoronavirus sub-genera: Decacovirus, Duvinacovirus, Rhinacovirus, Setracovirus and Minunacovirus and for Betacoronavirus sub-genera: Sarbecoviruses, Merbecovirus and Hibecovirus. Our results showed an overall proportion for CoV positive PCR tests of 23.7% at Chirundu site and 16.5% and 38.9% at Magweto site for insectivorous bats and Macronycteris gigas, respectively. Conclusions: The higher risk of bat coronavirus exposure for humans was found in December to March in relation to higher viral shedding peaks of coronaviruses in the parturition, lactation and weaning months of the bat populations at both sites. We also highlight the need to further document viral infectious risk in human/domestic animal populations surrounding bat habitats in Zimbabwe.